Kryzys modelu państwa neoliberalnego - Szymanowski, Rafał (Wydawnictwo Naukowe WNPiD UAM, 2016)
The article aims at analyzing the changing role of the state in the political economy after the Great Recession of 2008. The economic crisis that has unfolded since the collapse of the Lehman Brothers ignited a scientific debate about the role of the state in the economy. Scholars have argued that the 2008 crisis is not likely to be overcome simply with standard instruments of economic policy. Austerity measures and bank bailouts are not going to be sufficient, since the roots of the crisis are not merely economic but structural and multidimensional. Therefore overcoming the crisis will require bold political measures. Some analysts drew a parallel between the Great Recession and the Great Depression of the 1930s. The article presents the hypothesis, that the global economic crisis called into question the model of neoliberal state. New challenges rising in the aftermath of the 2008 economic crisis, like the danger of the secular stagnation, prolonged low economic growth, the lack of new disruptive innovations and diminishing number of really inclusive institutions require a more active state. After the Great Recession there is the need to reform institutional architecture of the market economy towards the greater inclusiveness and reshape the modern partnership between invisible hand of market and visible hand of government.
Keywords: kryzys państwa; państwo neoliberalne; neoliberalizm; polityka gospodarcza; globalny kryzys finansowy 2008; global financial crisis 2008; państwo liberalne; liberal state; państwo rozwojowe; developmental state; nowy instytucjonalizm; new institutionalism; sekularna stagnacja; secular stagnation; Wielkie Umiarkowanie; The Great Moderation; ekonomia; ekonomia kryzysu; deflacja długu; Hyman Minsky; Irving Fischer; system finansowy; finansjalizacja gospodarki; rozwój społeczno-gospodarczy; rynek; reżim regulacyjny; rządzenie